Drivers of Growth : Evidence from Sub-Saharan African Countries - Ghazanchyan, Manuk (IMF Working Papers; Working Paper ;, 2013)
This study examines the drivers of growth in Sub-Saharan African countries, using aggregate data, from the past decade. We correlate recent growth experience to key determinants of growth, including private and public investment, government consumption, the exchange regime and real exchange rate, and current account liberalization, using various econometric methodologies, including fixed and random effects models, with cluster-robust standard errors. We find that, depending on the specification, higher private and public investments boost growth. Some evidence is found that government consumption exerts a drag on growth and that more flexible exchange regimes are beneficial to growth. The real exchange rate and liberalization variables are not significant.